Study Regarding the Perception on the Personality Traits in Managerial Decision Making: Array - Rus, Mihaela; Tasențe, Tănase; Sandu, Mihaela Luminita (Journal of Danubian Studies and Research, 2020)
The decision-making process is “entirely dependent on the people and is a central activity of the manager, all other activities being undertaken to ensure correct decisions or, if the decision has already been taken, to implement and monitor its effectiveness”. Thus, managers are constantly required to evaluate alternatives and make decisions regarding a broad approach. Our research was carried out between April 20-30, 2019. An online questionnaire was applied, on a sample consisting of 30 managers, contractors or employees with execution functions. The main research objectives are: analyzing the main personality traits of a manager and identifying how these personality traits can influence managerial decision. To achieve the research objectives, we will analyze the perception of personality traits for a good manager, according to the following indicators: (1) dominance, (2) selfcontrol, (3) psychological well-being, (4) capacity for status, (5) community, (6) social conformity, (7) empathy, (8) flexibility, (9) conceptual fluency, (10) positive impression, (11) self-confidence, (12) independence, (13) psychological intuition, (14) social presence, (15) achievement through independence, (16) achievement through conformity, (17) responsibility, (18) sensitivity, (19) sociability, (20) tolerance.